The Validity of Sanctions Arrangements in Regional Regulations - Astariyani, Ni Luh Gede; Hattori, Mariko; Hanum , Willy Naresta (Lembaga Contrarius Indonesia, 2024)
The principle of lower-level legislation in the hierarchy of legislation must not conflict with higher-level regulations and must be enforced. This includes regional regulations whose administrative sanction content must not deviate from higher-level regulations. This study aims to determine the validity of regional regulations in regulating the content of sanctions, the regulation of sanctions for regional head regulations that do not comply with the rules above them, and how binding they are when applied. The research method used is the normative legal method, including the approach to legislation and legal concepts. The comparative method is also used to compare this issue with Japan. The results of this study indicate that there is disharmony between regional regulations and their implementing regulations due to the lack of detailed regulations on the content of regional head regulations, which has the potential to cause deviations in the content and affect the validity of the legal product. This has a negative impact and confuses at the implementation level, especially on the content of sanctions that are not in sync with the rules above them. Meanwhile, in Japan, Japanese administrative sanctions are contained in a very structured and standardized manner to minimize inconsistencies in regulations at the regional level. Therefore, the formation of material content regarding sanctions in implementing regulations must be based on legal validity, both materially and formally.